Is it important to palpate lymph nodes in open surgery for colorectal cancer?. Issue 2 (8th November 2016) - Yamaoka, Yusuke; Kinugasa, Yusuke; Shiomi, Akio; Yamaguchi, Tomohiro; Kagawa, Hiroyasu; Yamakawa, Yushi; Furutani, Akinobu; Numata, Masakatsu
Abstract: Introduction: In laparoscopic or robotic surgery, surgeons cannot directly palpate lymph nodes (LN), which could be considered a shortcoming in that procedure. This study was performed to evaluate the importance of palpation diagnosis of LN metastasis in colorectal cancer surgery. Methods: This study enrolled 408 patients who underwent curative resection for primary colorectal cancer in our department in 2014. The diameter of each manually dissected LN was measured, and the LN was then examined by palpation to determine whether it was metastatic based on its consistency. The palpation and pathological diagnoses of each LN were compared. Sensitivities, specificities, positive predictive values, negative predictive values, and accuracies were calculated for palpation diagnosis of LN metastasis in a node‐by‐node analysis, according to LN size. Results: Of the 13 750 dissected LN, 444 LN (3.2%) were metastatic. Overall, palpation diagnosis of LN metastasis revealed node‐by‐node sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of 50%, 98%, 52%, 98%, and 97%, respectively. The sensitivity for LN 3 mm and smaller and for LN 15 mm and larger was 3% and 90%, respectively. Conclusion: Palpation diagnosis of LN metastasis in colorectal cancer surgery was unreliable. Although poor haptics is considered to be a disadvantage in laparoscopic and robotic surgery, they are not inferior to open surgery in terms of LN dissection.